Changes in Care Associated with the Introduction of a Postpartum Hemorrhage Patient Safety Program - Lappen, Justin R.; Seidman, Dominika; Burke, Carol; Goetz, Kris; Grobman, William A. (American Journal of Perinatology, 2013)
Objective To determine whether the introduction of a postpartum hemorrhage (PPH) patient safety program was associated with changes in patient care or outcomes.Study Design A multipronged patient safety program regarding PPH was instituted at a tertiary care maternity hospital. Patient care and outcomes were assessed for 6 months prior to (period A) and 6 months after (period B) program institution.Results In all, 278 and 341 women were diagnosed with PPH during periods A and B, respectively. Women who had a PPH after the program were more likely to receive more than one dose of prostaglandin F2 α (24% versus 9%, p = 0.01) and more than one type of uterotonic (34% versus 25%, p = 0.02) and to have a B-lynch suture placed (9.4% versus 4.7%, p = 0.03). The frequency of blood transfusion, hysterectomy, and intensive care unit admission were similar between periods.Conclusion Introduction of a PPH safety program resulted in several indications of a more quickly escalated response.
Keywords: patient safety; postpartum hemorrhage; protocol